Analisis kemampuan koneksi matematis siswa berdasarkan self-confidence siswa Kelas VIII Sekolah Menengah Pertama - Ulfa, Desnani; Maimunah, Maimunah; Roza, Yenita (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
This research was conducted due to the fact that the level of mathematical connection ability of junior high school students was still relative low. This study aims to describe students' mathematical connection abilities based on students' self-confidence, especially in the topic of building flat sides. Self-confidence is one of the psychological aspects to see the success of learning in the school. The subjects of this study were the second grade students which is in the class VIII B as many as 25 people from SMP Negeri 3 Bangkinang. This research used a descriptive method with a qualitative approach. The instruments used in this study include a mathematical connection ability test and a self-confidence questionnaire. The stages of the research consista of 4 stages, namely: 1) filling out the self-confidence questionnaire, 2) giving mathematical connection ability test questions, 3) analyzing the data, and 4) drawing the conclusions. The results of the research has shown that: 1) Overall students' mathematical connection abilities get an average of 57%, which means that students' mathematical connection abilities are in a fairly good category, 2) Students with high self-confidence have an average mathematical connection ability of 60 %, 3) Students with moderate self-confidence have an average mathematical connection ability of 58.6%, 4) Students with low self-confidence have an average mathematical connection ability of 52.6% which is included in the poor category. Based on the results of the study, it can be concluded that students who have high self-confidence have better mathematical connection abilities rather than students who have moderate and low self-confidence.